Working fluids selection from perspectives of heat source and expander for a Trilateral cycle. (February 2019) - Chang, Nini; Zhu, Jialing; Chen, Guibing; Zhang, Peipei; Song, Anda
Abstract: This paper selects the working fluids for Trilateral cycle from two unique perspectives. The first aspect is to match the heat sources temperature with the critical temperature of working fluids, in which the thermal efficiency, exergy efficiency and utilization of heat source are chosen as the evaluation indicators. A better performance can be achieved when the heat source temperature approaches to the critical temperature of working fluid. From the aspect of expander, working fluids are selected to reduce volumetric flow ratio of expander and the size of expander, which have the lager vapor pressure at condensing temperature (VP), lager density at expander outlet and lower critical temperature. N-butane and R152a show higher net power output and lower volumetric flow ratio of expander among 13 studied working fluids. Two functions of expander volumetric flow ratio with respect to critical temperature of working fluid and VP have been gotten respectively. Furthermore, it can be concluded the suitable heat source temperature range of a TLC system is moderate temperature.